Ethnosocial Stratification in the Russian Colony Ross in California (1812-1841) - A. A. Istomin (Научный диалог)
Ethnosocial stratification of the population of the Russian colony of Ross (now Fort Ross), which existed in California in 1812-1841 as an outpost of the Russian-American company is considered. A general description of the population of the Ross colony, its distribution, and ethno-demographic structure in its dynamics is given. The author concludes that in Ross the diversity of the ethnic composition of the population was combined with its quite clear (although sometimes somewhat conditional) ethnosocial stratification according to the type common to all of Russian America, based on a combination of ethnic and vocational educational features. It is shown that the individual’s place in this stratification was determined by the differentiation of the colonialists and indigene, the degree of cultural and state-political proximity to the colonial elite, the production qualifications, the form and amount of payment associated with it. The author identifies five ethno-social strata as part of the Ross population: the administrative elite; Russian workers (“industrial”), which the Finnish and Yakut adjoined to; creoles (mestizos) and natives “in the service of the Company”; Aleuts dependent on the Russian-American company (mainly Kodiak Eskimos); local Indians, who became the “foundation” of the social pyramid. The most fundamental differences between the strata and the socio-historical nature of the system of exploitation of the Californian Indians are considered.